2021
DOI: 10.7759/cureus.13890
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Ticagrelor-Induced Bullous Fixed Drug Eruption

Abstract: We describe a case of a suspected cutaneous hypersensitivity reaction to ticagrelor. The patient displayed a localized bullous fixed drug eruption after being loaded with ticagrelor, which resolved with oral antihistamines and topical steroids after one week. Clopidogrel and rivaroxaban were successfully administered as alternative antithrombotic therapy without any apparent further hypersensitivity skin reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The case reported by Quinn et al demonstrated very similar skin biopsy findings showing perivascular lymphocytic infiltrates compared to our patient but did not comment on necrotic keratinocytes as seen in our biopsy [3]. The four other reports showed different dermatological reactions with one case of exanthematous pustulosis [5], one case of eccrine hidradenitis [6], one case of a bullous fixed drug eruption [7], and a case of Sweet syndrome [8]. These cases are described in Table 1.…”
Section: Discussionsupporting
confidence: 81%
“…The case reported by Quinn et al demonstrated very similar skin biopsy findings showing perivascular lymphocytic infiltrates compared to our patient but did not comment on necrotic keratinocytes as seen in our biopsy [3]. The four other reports showed different dermatological reactions with one case of exanthematous pustulosis [5], one case of eccrine hidradenitis [6], one case of a bullous fixed drug eruption [7], and a case of Sweet syndrome [8]. These cases are described in Table 1.…”
Section: Discussionsupporting
confidence: 81%
“…Fixed drug eruption is recognized as repeatedly erythematous pigmented plaques following the same causative agents between 30 minutes and eight hours (on average two hours). Blisters occasionally occur on fixed drug eruptions [ 4 ] and can also spread widely and cause systemic symptoms including fever [ 5 ]. These clinical features might resemble Stevens-Johnson syndrome or toxic epidermal necrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the clinical features of these patients. 5–11 All 7 patients were male who were 44–73 years of age; 4 presented with acute coronary syndrome, whereas 2 had stable angina, and 5 of 6 patients in the case reports had undergone a PCI with a drug-eluting stent. Hypersensitivity manifestations included rash (n = 4), urticaria (n = 1), angioedema (n = 2), periorbital edema (n = 1), and hemorrhagic bullae (n = 2).…”
mentioning
confidence: 99%